Is the Self in Hume Overmoralized? - Garral, Michael D. (Revista de Filosofía, 2007)
Despite being averse to moral extravagance, Hume’s own conception of morality threatens to be too demanding and his view of human life to be too moralistic. The problem lies in the scope (and concomitantly the content) Hume assigns morality, the effect of which is the apparent exclusion of the morally indifferent and the morally supererogatory. This threatens to render the normative dimension of Hume’s account problematic. Sufficiently problematic to overmoralize the self? That is the question this essay seeks to motivate.